Incisional Hernia in a 12-mm Nonbladed Trocar Site Following Laparoscopic Nephrectomy - Erik J. Kouba; J. Slade Hubbard; Eric Wallen; Raj S. Pruthi (The Scientific World Journal)
Non-bladed trocars and radially dilating systems are considered less traumatic to the abdominal wall because they do not incise the fascia itself. Since the fascia is not cut, it has believed that the fascia closes by itself. Consequently, several authors have suggested that closure of the abdominal fascia may be unnecessary when such non-bladed laparoscopic trocars are used. We report of a case in which a port site hernia was diagnosed at the site of a 12 mm non-bladed trocar 11 days after laparoscopic nephrectomy. Although it may be true that in many cases port site closure is unnecessary and does not result in bowel herniation, this case along with a prior report serve as important reminders that port site hernias are possible even in the use of non-bladed or radial dilating systems, and that there exists a number of potential variables that may predispose to herniation and consequently the ability to predict such events in individual patients remains uncertain. As such, we recommend closing 10 mm or larger port sites irrespective of trocar design.